Fade margin estimation technique using radar data for satellite link - Badron, Khairayu; Ismail, Ahmad Fadzil; Asnawi, Ani Liza; Wan Nordin, Mimi Aminah; Mohd. Isa, Farah Nadia (Springer, 2015)
The fade margin is an important parameter used by the operator to measure the link availability for a given time. Fade margin is a parameter that is used in the design of satellite links to ensure optimal performance of the link. A new technique is proposed where the fade margin of a satellite link can be estimated using attenuation statistics of radar data. Data set acquired from Malaysian meteorological radar for the year 2009 is used in the study. Radar return or reflectivity is used in the process of generating the attenuation values. The reflectivity is first converted into rainfall rate value and the specific attenuation is then calculated. The rain attenuation values can be derived by the multiplication of the specific attenuation and the path length affected. The rainfall rate derived from radar information is used in calculating the slant path attenuation of the satellite link. The databases of rain attenuation is then compiled with the time duration to acquire the cumulative distribution function (CDF) for the specified link. The satellite link investigated are based on the RazakSAT link in relation to its ground station located at Sg Lang, Banting, Selangor, Malaysia for X-band and MEASAT-3 satellite in relation to its ground station at Cyberjaya, Selangor, Malaysia for Ku-band.